UZBEK EFL STUDENTS’ ETHICAL RESPONSES TO AI-GENERATED FEEDBACK IN ACADEMIC WRITING - Ozodakhon Izzatillaeva (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2026)
Artificial intelligence is now widely used in academic writing, especially through tools that give automated feedback. AI-generated feedback can help students improve their writing. However, it also raises ethical questions about academic honesty and authorship. This study examines how Uzbek EFL students respond ethically to AI-generated feedback in academic writing. It focuses on their ethical judgments and their writing practices. The study used a quantitative survey design. Data were collected from 40 Uzbek EFL students studying at universities in Uzbekistan. The questionnaire included scenario-based questions and Likert-scale items. These items were designed based on Rest’s model of ethical decision-making and feedback literacy theory. Descriptive statistical analysis was used to identify patterns in students’ ethical judgments and actions. The results show that most students consider AI-generated feedback ethically acceptable when they remain in control of their writing and use the feedback selectively. Many students clearly distinguished between AI-generated feedback and AI-generated text, and they viewed feedback as less ethically problematic. However, many students also reported ethical uncertainty, especially when AI made extensive revisions or when institutional rules were unclear. While many students said they rewrote AI feedback in their own words, some admitted that they accepted AI suggestions without making changes. This study adds to the limited research on AI ethics in Central Asia. It also shows the need for clearer institutional guidance on the ethical use of AI-generated feedback in EFL academic writing.